Incidence of virus diseases in maize fields in the Trakya region of Turkey - Ilbağı, Havva; Rabenstein, Frank; Habekuss, Antje; Ordon, Frank; Çıtır, Ahmet (Phytoprotection, 2006)
AbstractA survey on maize virus diseases was conducted in the Trakya region of Turkey by examining 32 496 and 46 871 plants in 2004 and 2005, respectively. Rates of symptomatic plants were estimated at 3.7 to 63.6%, depending on locations. Biological and serological test results revealed the presence of barley yellow dwarf virus-PAV (BYDV-PAV), maize dwarf mosaic virus (MDMV), sugarcane mosaic virus (SCMV), and Johnson grass mosaic virus (JGMV). One hundred forty-two samples were collected randomly from 6492 symptomatic plants in 2004. Seventy-two out of the 142 samples were infected with MDMV, two were infected with BYDV-PAV, 19 with MDMV and BYDV-PAV, two with MDMV, BYDV-PAV and SCMV, and only one sample contained the four viruses. In 2005, 100 other leaf samples were collected randomly from 11 739 symptomatic maize plants. Serological tests revealed that 50% of the samples were infected with MDMV and SCMV; however, five showed mixed infections of two or three combinations of tested viruses. Individual MDMV, SCMV, BYDV-PAV and JGMV infections were detected in five, three, two and four samples, respectively. Presence of MDMV was confirmed by Western blot analysis and IC-RT-PCR. SCMV was also detected by IC-RT-PCR. This is the first study reporting the detection of SCMV and JGMV on maize plants in Turkey.